2015
DOI: 10.3141/2506-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Binder Blending

Abstract: The current tendency in the asphalt paving industry is to increase the use of recycled asphalt pavement (RAP) and recycled asphalt shingles (RAS). However, a major concern that limits the use of RAP or RAS is the uncertainty about how much of the aged binder in RAP or RAS can be blended into virgin binder. Studies have focused on the diffusion between old and new binders. However, little research has been conducted to determine how much recycled binder could be mobilized and made available to coat aggregates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…These concepts seem to be widely recognised by the scientific community, however the results of a literature review (Table 1) highlighted that practitioners have not yet achieved a general consensus on the terms related to the blending phenomena and authors use concepts and terms interchangeably. Amongst these: blending efficiency (Bowers, Huang, Shu, & Miller, 2014;Bowers, Moore, Huang, & Shu, 2014;Xu, Hao, Zhang, & Yuan, 2018), blending status (Zhao, Huang, Shu, & Woods, 2016), blending ratio (Delfosse, Drouadaine, Largeaud, & Dumont, 2016), rate of intermixing (Oliver, 2001), binder transfer (Zhang, Wen, & Hobbs, 2015), mobilization rate (Bressi et al, 2015;Ding, Huang, & Shu, 2018;Vassaux et al, 2018;Zhao, Huang, Shu, & Woods, 2015), meso-blending (Gundla & Underwood, 2015) and the most used terminology by far degree of blending (DoB) (Abd, Al-Khalid, & Akhtar, 2018;Al-Qadi et al, 2009;Booshehrian, Mogawer, & Bonaquist, 2013;Castorena, Pape, & Mooney, 2016;Cavalli, Partl, & Poulikakos, 2017;Coffey, Dubois, Mehta, & Purdy, 2013;Gaitan et al, 2013;Kriz et al, 2014;Liphardt, Radziszewski, & Król, 2015;Mogawer, Booshehrian, Vahidi, & Austerman, 2013;Mogawer et al, 2012;Navaro et al, 2012;Norton et al, 2014;Rinaldini, Schuetz, Partl, Tebaldi, & Poulikakos, 2014;Shirodkar et al, 2013Shirodkar et al, , 2011Stephens, Mahoney, & Dippold, 2001). (Vassaux et al, 2019) "Blend" presents the ability of two components to create a homogenous product where the chemical composition is identical everywhere at the scale observation of the study.…”
Section: Mineralmentioning
confidence: 99%
See 1 more Smart Citation
“…These concepts seem to be widely recognised by the scientific community, however the results of a literature review (Table 1) highlighted that practitioners have not yet achieved a general consensus on the terms related to the blending phenomena and authors use concepts and terms interchangeably. Amongst these: blending efficiency (Bowers, Huang, Shu, & Miller, 2014;Bowers, Moore, Huang, & Shu, 2014;Xu, Hao, Zhang, & Yuan, 2018), blending status (Zhao, Huang, Shu, & Woods, 2016), blending ratio (Delfosse, Drouadaine, Largeaud, & Dumont, 2016), rate of intermixing (Oliver, 2001), binder transfer (Zhang, Wen, & Hobbs, 2015), mobilization rate (Bressi et al, 2015;Ding, Huang, & Shu, 2018;Vassaux et al, 2018;Zhao, Huang, Shu, & Woods, 2015), meso-blending (Gundla & Underwood, 2015) and the most used terminology by far degree of blending (DoB) (Abd, Al-Khalid, & Akhtar, 2018;Al-Qadi et al, 2009;Booshehrian, Mogawer, & Bonaquist, 2013;Castorena, Pape, & Mooney, 2016;Cavalli, Partl, & Poulikakos, 2017;Coffey, Dubois, Mehta, & Purdy, 2013;Gaitan et al, 2013;Kriz et al, 2014;Liphardt, Radziszewski, & Król, 2015;Mogawer, Booshehrian, Vahidi, & Austerman, 2013;Mogawer et al, 2012;Navaro et al, 2012;Norton et al, 2014;Rinaldini, Schuetz, Partl, Tebaldi, & Poulikakos, 2014;Shirodkar et al, 2013Shirodkar et al, , 2011Stephens, Mahoney, & Dippold, 2001). (Vassaux et al, 2019) "Blend" presents the ability of two components to create a homogenous product where the chemical composition is identical everywhere at the scale observation of the study.…”
Section: Mineralmentioning
confidence: 99%
“…Furthermore, analysing the many factors identified, it was recognised that some are linked to the design and manufacturing of the asphalt mixture containing RA (Table 2), while some others are strictly related to the RA (Table 3). Kriz et al, 2014;Lo Presti et al, 2015;Nahar et al, 2013;Navaro et al, 2012;Oliver, 2001;Rad, Sefidmazgi, & Bahia, 2014;Stephens et al, 2001;Zhang et al, 2015;Zhao et al, 2015).…”
Section: Mineralmentioning
confidence: 99%
“…Recent theoretical and practical achievements enable the recycling of up to 100% of RAP, of course, we need to evaluate that the studies were conducted in ideal and lab-controlled conditions [44,45]. RAP inhomogeneity has a huge impact on its maximum permitted percentage in a recycled RHMA.…”
Section: Model Of Technologies Of Rap Recyclingmentioning
confidence: 99%
“…Plenty of research efforts have been conducted on the impact of some waste materials (e.g., RAP, GTR, and waste concrete and brick) on the performance of the roads through laboratory and field tests. For example, the researchers reported that RAP improved the rutting resistance [3][4][5][6][7][8] and GTR improved the resistance to permanent deformation and cracking of the asphalt mixtures [9][10][11][12][13]. Jia et al [14] presented the use of construction and demolition wastes in LVRs and indicated using them in the base and subbase is feasible for low-volume roads if the mix design is appropriate.…”
Section: Introductionmentioning
confidence: 99%